2019
DOI: 10.1038/s41531-019-0083-7
|View full text |Cite
|
Sign up to set email alerts
|

Vertical saccades and antisaccades: complementary markers for motor and cognitive impairment in Parkinson’s disease

Abstract: Previous studies provide partly contradictory results about the characteristics of saccades in PD and the possible effects of levodopa, which may be attributed to different study design regarding disease stages, medication state or cognitive functioning. We studied horizontal and vertical visually guided saccades (VGS) and antisaccades (AS) in 40 patients with PD with and without postural instability in On and Off medication state as well as in 20 healthy controls (HC). Motor and cognitive performance were ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(55 citation statements)
references
References 27 publications
5
49
1
Order By: Relevance
“…While some studies demonstrated increased antisaccade error rates even in unmedicated patients in very early disease stages (Antoniades et al, 2015a;Hanuška et al 2019), others found no significant alterations of antisaccade latency or antisaccade error rate early and later in the disease course. (Ranchet et al, 2017;Nagai et al, 2019) As proposed by two recent studies (Lu et al, 2019;Waldthaler et al, 2019a), antisaccade latency might correlate with disease duration in PD without significant impact of dopaminergic medication.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…While some studies demonstrated increased antisaccade error rates even in unmedicated patients in very early disease stages (Antoniades et al, 2015a;Hanuška et al 2019), others found no significant alterations of antisaccade latency or antisaccade error rate early and later in the disease course. (Ranchet et al, 2017;Nagai et al, 2019) As proposed by two recent studies (Lu et al, 2019;Waldthaler et al, 2019a), antisaccade latency might correlate with disease duration in PD without significant impact of dopaminergic medication.…”
Section: Introductionmentioning
confidence: 92%
“…CI confidence interval, HC healthy control group, PD group with Parkinson's disease, (m) mixed task design with prosaccades and antisaccades, SD standard deviation, Std. standardized ◂ (Briand et al, 1999), B14 (Bonnet et al, 2014b), B19 (Barbosa et al, 2019), C12 (Cameron et al, 2012), C00 (Crevits et al, 2000), E17 (Ewenczyk et al, 2017), G16 (Gorges et al, 2016), H10 (Harsay et al, 2010), H19 (Hanuška et al, 2019), L19 (Lu et al, 2019), L90 (Lueck et al, 1990), L16 (Lemos et al, 2016), M05 (Mosimann et al, 2005), N16 (Nemanich & Earhart, 2016), N19 (Nagai et al, 2019), R17 (Ranchet et al, 2017), RP15 (Rivaud-Péchoux et al, 2007), V19 (Visser et al, 2019), vK09 (van Koningsbruggen et al, 2009, W15 (Walton et al, 2015), W16 (Wang et al, 2016), W19 (Waldthaler et al, 2019a)…”
Section: Moderator Analysismentioning
confidence: 99%
“…Although carbidopa-levodopa has been shown to improve saccade latency, 19 , 24 recent on vs. off studies indicate that in some patients, carbidopa-levodopa can lead to worsening of reflexive saccade latencies. 20 , 21 , 29 , 53 In our patient, these freezing episodes were observed as early as 2 hours after taking carbidopa-levodopa, so we cannot rule out the potential contribution of this medication. In addition, clonazepam, a benzodiazepine, has been associated with increased saccadic latency.…”
Section: Discussionmentioning
confidence: 72%
“… 15 , 16 , 17 Although the effect of dopamine replacement on reflexive saccade latencies has been mixed, 19 , 20 , 21 treatment has been shown to improve the latency of volitional saccades. 19 , 20 , 21 , 22 , 23 Subthalamic deep brain stimulation has also been shown to improve saccade latencies. 24 , 25 , 26 …”
Section: Introductionmentioning
confidence: 99%
“…Both tests require a suppression of reflexive pro-saccades and engage a complex network of brain regions, including dorsolateral prefrontal cortex, frontal eye fields, and supplementary eye fields, basal ganglia, superior colliculus and cerebellum (3335). The anti-saccade task has been used to characterize cognitive impairments in patients with schizophrenia (36,37), dementia (38), Parkinson’s disease (39) and cerebellar atrophies (40). In the anti-saccade and anti-tapping tests, both APDS patients underperformed controls (anti-saccade performance: P1 = 43%, C1 = 89%, P2 = 50%, C2 = 74%; anti-tapping performance: P1 = 31%, C1 = 88%, P2 = 50%, C2 = 83%) (Fig.…”
Section: Resultsmentioning
confidence: 99%